Hypoxia inducible factor 1α signaling in fractionated radiation-induced lung injury: role of oxidative stress and tissue hypoxia - Rabbani, Zahid; Mi, J.; Zhang, Y.; Delong, M.; Jackson, I. L.; Fleckenstein, Katharina; Salahuddin, F. K.; Zhang, X.; Clary, B.; Anscher, M. S.; Vujaskovic, Z. (Radiation research, 2010)
To investigate the relationship of HIF1α signaling to oxidative stress, tissue hypoxia, angiogenesis and inflammation, female Fischer 344 rats were irradiated to the right hemithorax with a fractionated dose of 40 Gy (8 Gy × 5 days). The lung tissues were harvested before and at 4, 6, 10, 14, 18, 22 and 26 weeks after irradiation for serial studies of biological markers, including markers for hypoxia (HIF1α, pimonidazole and CA IX), oxidative stress (8-OHdG), and angiogenesis/capillary proliferation (VEGF/CD 105), as well as macrophage activation (ED-1) and cell signaling/fibrosis (NFκB, TGFβ1), using immunohistochemistry and Western blot analysis. HIF1α staining could be observed as early as 4 weeks postirradiation and was significantly increased with time after irradiation. Importantly, HIF1α levels paralleled oxidative stress (8-OHdG), tissue hypoxia (pimonidazole and CA IX), and macrophage accumulation consistent with inflammatory response. Moreover, changes in HIF1α expression identified by immunohistochemistry assay parallel the changes in TGFβ1, VEGF, NFκB and CD 105 levels in irradiated lungs. These results support the notion that oxidative stress and tissue hypoxia might serve as triggering signals for HIF1α activity in irradiated lungs, relating to radiation-induced inflammation, angiogenesis and fibrosis.